Comparison of shortwave radiation dynamics between boreal forest and open peatland pairs in southern and northern Finland - O. Peräkylä; E. Rinne; E. Ezhova; A. Lintunen; A. Lintunen; A. Lohila; A. Lohila; J. Aalto; J. Aalto; M. Aurela; P. Kolari; M. Kulmala (Biogeosciences)
Snow cover plays a key role in determining the albedo and thus the shortwave radiation balance of a surface. The effect of snow on albedo is modulated by land use: tree canopies break the uniform snow layer and lower the albedo as compared to an open ground. This results in a higher fraction of shortwave radiation being absorbed in forests. At seasonally snow-covered high latitudes, this lowering of the albedo has been suggested to offset some or all of the climate cooling effect of the carbon stored by forests. We used long-term in situ measurements to study the albedo and shortwave radiation balance of two pairs of sites, each consisting of an open peatland and a forest. One pair is located in northern and one in southern Finland in the boreal zone. We found that both forest sites had a low, constant albedo during the snow-free period. In contrast, both peatland sites had a higher snow-free albedo, with a clear seasonal cycle. The albedo was found to depend on the diffuse fraction of the incoming radiation: during the snow-covered period, higher diffuse fraction was associated with lower albedo, while during the snow-free period it was associated with higher albedo. The thinning of the southern forest site, resulting in a significant reduction of the leaf area index, increased the albedo especially in the snow-covered period. During the snow-covered period, the peatland sites again had higher albedo than the forest sites. The transition between the high and low albedo upon snow accumulation and especially snowmelt was more abrupt at the peatland sites. In the northern pair, the forest site absorbed on average 0.47 GJ m−2 more (around 23 % more) energy from net shortwave radiation than the peatland site annually, whereas in the southern pair, the forest site absorbed on average 0.37 GJ m−2 more (around 14 % more) than the peatland site. The difference in the annual absorbed energy between the peatland site and the forest site was greater in the northern pair due to longer snow-cover duration. This was partially offset by the greater difference in snow-free albedos and higher solar radiation at the southern site pair. The annual difference in the absorbed shortwave radiation between the forest site and the peatland site varied considerably between the years (from 0.37 to 0.61 GJ m−2 for the northern pair and from 0.20 to 0.53 GJ m−2 for the southern pair). The annual variation was mainly controlled by the snow-cover duration in the spring at the peatland sites. These findings have implications for the future climate, as snow cover continues to evolve under global warming.